Strategi Komunikasi Pemasaran Angkringan Khulo Melalui Media Sosial Instagram - Haikal Ibnu Hakim; Noviawan Ohorella; Edy Prihantoro (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
This study aims to determine the marketing communication strategy of Angkringan Khulo through Instagram social media. With Instagram angkringan, Khulo can do marketing and promotions including posting photos of food and beverage products through Instagram social media. The research method used is descriptive qualitative. The data used in this study consisted of primary data and secondary data. The theory used is Integrated Marketing Communication Theory. Data collection techniques used are observation, interviews, and documentation. Based on the results of the research that the marketing communication strategy carried out by Angkringan Khulo is considered appropriate. The marketing communication strategy carried out by Angkringan Khulo is through Instagram social media by posting photos of food and beverage products with an interesting and funny caption, by marketing through Instagram social media, everyone can access and find out the location of Khulo Angkringan quickly, therefore Angkringan Khulo uses social media Instagram as a promotional tool in order to create the desired target and the occurrence of high buying interest. The suggestion that researchers can give is that there should be more posts on the Angkringan Khulo Instagram account and the @angkringankhulo Instagram account, and they must maintain good relations with each of their consumers.